Nitrogen and potassium fertilization of 'Nanicao' banana (Musa AAA Cavendish subgroup) under irrigated and non-irrigated conditions - Teixeira, L. A J; Natale, W. [UNESP]; Ruggiero, C. [UNESP] (My University, 2002)
A field experiment was carried out in São Paulo State, Brazil, with the objective of investigating the response of 'Nanicao' banana (Musa AAA Cavendish subgroup) to nitrogen and potassium fertilization under irrigated and non-irrigated conditions during two crop seasons. The effects of cropping on some soil chemical properties were also investigated. A split-plot design was used with irrigation (micro-sprinkler) and no irrigation applied to main plots, and a combination of four rates of N (0, 200, 400 and 800 kg N ha-1) and K (0, 300, 600 and 900 kg K2O ha-1) as the sub-plot treatments. Irrigation caused a significant increase in fruit yield and determined the response to N and K fertilizers. In spite of a high level of exchangeable K, a positive response to K application was observed on the plant crop in non-irrigated plants. Fruit yield was impaired by N application in the plant crop (1st cycle). A positive response to N application was observed in the 2nd cycle. Soil pH decreased with increasing N rates. Exchangeable K was significantly reduced due to crop exhaustion.
Keywords: Irrigation; K; N; Nutrition; PH; Sustainability